Revisitando a síntese de uma Zn(II)-porfirina do tipo A3B como potencial fotossensibilizador para inativação fotodinâmica antimicrobiana - Soares Neto, João Gomes (2023)
Water-soluble Zn(II)-porphyrins (ZnPs) derived from 2-N-alkylpyridinioporphyrins, ZnTalkyl-2-PyP4+, have been widely explored as photosensitizers (PSs) in photodynamic therapy for the inactivation of microorganisms. The in vivo efficiency of Zn-porphyrins is related not only to photoredox activities (as a photosensitizer), but also to the increased lipophilicity of the molecule and its bioavailability. The synthesis of a new class of Zn(II) cationic porphyrins of the [ZnA3B]3+ type (A = 2-N-methylpyridyl, B = O-alkylvanillin) was previously performed in the UFPB group and there was an increase in the retention factor (Rf), which has typically been correlated with lipophilicity in cationic metalloporphyrins. In the present study, the synthesis of ZnP of the type [ZnA3B]3+, 5-(3,4-dimethoxyphenyl)-10,15,20-tris(N-pyridinium-2-yl)porphyrinatozinc(II) (ZnMVanTriM-2-PyP3+), was revisited. The complex obtained was characterized by UV-vis spectroscopy, obtaining yields greater than 90%, with UV-Vis spectra characteristic of those reported in the literature with a wavelength of 428 nm, and 1H NMR pointing to the disappearance of internal hydrogens. Analysis by thin layer chromatography (TLC-SiO2) confirmed an increase in lipophilicity, being similar to that of larger porphyrins of the [ZnA4]4+ type, such as meso-tetrakis(N-n-butylpyridinium-2-yl)porphyrinatezinc(II), which are already considered by the literature as potent photodynamic agents with good bioavailability.